Quantification of drug-induced fractional killing using high-throughput microscopy - Zintis Inde; Jason Rodencal; Scott J. Dixon (STAR Protocols, 2021)
Summary: Anti-cancer drugs kill only a fraction of cells within a population at any given time. Here, we describe a protocol to quantify drug-induced fractional killing over time using high-throughput imaging. This protocol can be used to compare the effect of hundreds of conditions in parallel. We show how this protocol can be used to examine fractional killing in response to inhibitors of the mitogen-activated protein kinase pathway.For complete details on the use and execution of this protocol, please refer to Inde et al. (2020).